2021
DOI: 10.3389/fimmu.2021.667690
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pathogenesis of Psoriasis Complicated With Atherosclerosis via Microarray Data Analysis

Abstract: BackgroundAlthough more and more evidence has supported psoriasis is prone to atherosclerosis, the common mechanism of its occurrence is still not fully elucidated. The purpose of this study is to further explore the molecular mechanism of the occurrence of this complication.MethodsThe gene expression profiles of psoriasis (GSE30999) and atherosclerosis (GSE28829) were downloaded from the Gene Expression Omnibus (GEO) database. After identifying the common differentially expressed genes (DEGs) of psoriasis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…PPI network of DEGs was constructed by STRING (11.0b; https://string-db.org/ ) with a combined score > 0.9 as the cut-off point (Kwon et al, 2018 ). Hub genes were identified using cytoHubba (Su et al, 2021 ), a plug-in of Cytoscape software (Cytoscape, 3.8.2), and significant modules in the PPI network were identified by MCODE 2.0.0 (Azad et al, 2018 ), another plug-in of Cytoscape software. The parameters of DEGs clustering and scoring were set as follows: MCODE score ≥ 4, degree cut-off = 2, node score cut-off = 0.2, max depth = 100, and k-score = 2.…”
Section: Methodsmentioning
confidence: 99%
“…PPI network of DEGs was constructed by STRING (11.0b; https://string-db.org/ ) with a combined score > 0.9 as the cut-off point (Kwon et al, 2018 ). Hub genes were identified using cytoHubba (Su et al, 2021 ), a plug-in of Cytoscape software (Cytoscape, 3.8.2), and significant modules in the PPI network were identified by MCODE 2.0.0 (Azad et al, 2018 ), another plug-in of Cytoscape software. The parameters of DEGs clustering and scoring were set as follows: MCODE score ≥ 4, degree cut-off = 2, node score cut-off = 0.2, max depth = 100, and k-score = 2.…”
Section: Methodsmentioning
confidence: 99%
“…The Cytoscape software (version 3.6.1) was applied to visualize the PPI network ( Shannon et al, 2003 ). Besides, the Molecular Complex Detection (MCODE) plugin in the Cytoscape software was used to identify the interesting modules (selection criteria: degree cutoff = 2, K-core = 2, and node score cutoff = 0.2) ( Bader and Hogue, 2003 ; Bandettini et al, 2012 ; Su et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Lu et al noted the genetic similarity between psoriasis and CVD using single-nucleotide polymorphisms (SNPs) as risk indicators for CVD and psoriasis ( 46 ). Using the cyto-Hubba method, studies have recently identified 16 hub genes associated with these two diseases, in which 7 genes ( MMP9, CSF2RB, IL1RN, CCL5, CD53, NCF2 and TLR2 ) are upregulated in both psoriasis and atherosclerosis ( 47 ). Among them, the function of MMP9 gene is more closely related to IL-17 as IL-17 inhibitors can reduce the expression of MMP9 ( 48 ), and level of MMP9 has been also associated with chronic progress of psoriasis ( 49 , 50 ).…”
Section: Common Pathogenesis Of Psoriasis and Atherosclerosismentioning
confidence: 99%
“…Among them, the function of MMP9 gene is more closely related to IL-17 as IL-17 inhibitors can reduce the expression of MMP9 ( 48 ), and level of MMP9 has been also associated with chronic progress of psoriasis ( 49 , 50 ). Therefore, the pathogenic mechanisms of comorbid psoriasis and atherosclerosis are likely controlled by these hub genes ( 47 ). Animal models with gene knout out may be able to verify such comorbidity mechanisms at a genetic perspective.…”
Section: Common Pathogenesis Of Psoriasis and Atherosclerosismentioning
confidence: 99%